Ultrasound mediated luminescence tomography using contrast agents - Zhang, Qimei (2016)
The achievable spatial resolution of fluorescence and bioluminescence imaging in deep tissue is severely limited by strong tissue scattering and absorption. The hybrid technique ultrasound (US) mediated fluorescence tomography (USMFT) has been investigated in the past decade, with the aim to obtain fluorescence images with optical contrast and US resolution. However, the very low modulation depth due to the intrinsic incoherent properties of fluorescence leads to low signal-to-noise ratio. In this thesis, the techniques of US mediated luminescence tomography (USMLT, including US mediated bioluminescence tomgoraphy (USMBLT) and USMFT) are investigated with the aim to improve the effect of US on light intensity via application of contrast agents. The mechanisms of USMBLT are firstly studied through incorporating the effect of US into NIRFAST, an open source software package for simulation of light propagation. The influence of US on optical properties (reduced scattering coefficient, absorption coefficient, and refractive index) and concentration of source particles are studied. Effects of US pressure, US position, and source particle concentration on the modulation depth are investigated and the signal-to-noise ratio for in vivo detection is calculated. It is demonstrated that the dominant effect in the generation of USMBL signal is US induced variation in the concentration of the source particles, and this effect is at least two orders of magnitude greater than that caused by changes in the optical properties. It is also found that modulation depth increases linearly with increase of US pressure. The maximum modulation depth can be obtained when the US focal zone overlaps the bioluminescence source region. The modulated fluence rate increases linearly with increase of the concentration but the modulation depth is independent of the concentration. Results for signal-to-noise ratio calculation confirm the feasibility of applying USMBLT in preclinical imaging of mice to improve the spatial resolution of bioluminescence imaging. Secondly, fluorophore labelled microbubbles are studied as a contrast agent to increase the modulation depth of USMFT. Upon application of US the size of the microbubbles oscillate changing the intermolecular distances of the fluorophores labelled on the monolayer of the microbubbles resulting in modulated fluorescence emission intensity. Increased modulation depth is observed both from simulation and experiment. The influence of factors including microbubble radius, US pressure, labelling concentration on the US modulated fluorescence emission are simulated. It was shown that the effects of the three factors are closely related to each other, and it is difficult to decouple their effects. Generally the maximum modulated signal can be obtained within the region C ∈ (2 mol% 5 mol%) and R0 ∈ (1.5μm 5μm). However microbubbles with a higher fluorophore labelling concentration or a bigger radius require higher US pressure to obtain its maximum volumeric oscillation and the highest modulated signal. The results suggest that it is desirable to produce microbubble suspensions with narrow size distribution, so that most of the microbubbles can be labelled by an optimized concentration and exposed to an appropriate US pressure. Thirdly, liposome based contrast agents are studied for use in USMFT for the first time. Compared with microbubbles, liposomes have the advantages that they have better stability, less US scattering, and can be manufactured with a defined size in nanometer scale. Liposomes are labelled with pyrene which has well-known concentration dependent excimer formation characteristic. The acousto-fluorescence dynamics of liposomes containing lipids with pyrene labelled on the fatty acid tail group (PyPC) and the head group (PyPE) were compared. An increase in excimer emission intensity following exposure to US was observed for both cases studied. The increased intensity and rise time constants were found to be different for the PyPC and PyPE labelled liposomes, and dependent on the applied US pressure and exposure time. The greatest US On-to-Off ratio of excimer emission intensity (130%) and smallest rise time constant (0.33 s) are achieved through the use of the PyPC labelled liposomes. Possible mechanisms underlying the observed increase of the excimer emission intensity in PyPC system is considered to arise from the "wagging" of acyl chains which involves fast response and requires lower US energy. This is accompanied with the increased lipid lateral diffusivity, mechanisms also active in the PyPE system. Finally, DiD-DiR labelled liposomes based on fluorescence resonance energy transfer (FRET) are studied. The excitation and emission spectra are located close or within near-infrared window, where the penetration depth is up to several centimetres. Measurements of emisison spectra show that strong FRET and self-quenching exist in the DiD-DiR labelled liposomes. The fluorescence emission intensity changes upon application of US, with the change trend dependent on fluorophore types, detection wavelength, and fluorophore concentration. Line scanning of a tube buried at a depth of 1 cm in a heavily scattering phantom shows a contrast of 8.5% can be obtained using 0.5 mol% DiD-DiR labelled liposomes through detection at DiR emission wavelength (around 740nm - 790 nm). The resolution can be improved by a factor of 6.3 compared with its no US counterpart. These results suggest that DiD-DiR labelled liposome has potential to be used as contrast agent of USMFT for deep tissue imaging. Further application for in vivo imaging is discussed.